Audio coding application - Chan, Gary Xin Hao (2015)
It can be said that the MP3 coding method is one of the best out there due to the different stages in the Mp3 compression method. One particular stage of great interest is the part on Psychoacoustic Model. It is emphasized in this model that there is this phenomenon of masking, which means that when two sounds are played simultaneously or almost simultaneously, the “softer” sound will be masked by the relatively louder one and will not be heard by the human ear. This brings us to the topic on Equal Loudness Curve or also known as Fletcher Munson curve, which gives credit to Harvey Fletcher and Wilden A. Munson who first came up with the experiment and published a paper about it. The bulk of this thesis would be to design and create, attempting to reproduce the Equal Loudness Curve, as well as the properties and important knowledge that we can obtain from this curve, using a high level language and interactive environment to analyse data and applications known as Matlab. Important properties such as the hearing range of humans and the different frequencies of sounds at their respective sound pressure levels which cause the human ear to perceive them as sounding as loud will then be discussed further in the Equal Loudness section. This experiment aims to bridge the gap between what is learnt in theory, together with what can be obtained in practice through an experiment of such. The experiment data and values will then also be tabulated in the subsequent sections to validate the various findings and properties that should be obtained from the equal loudness curve. Only with the data and values can we further appreciate the psychoacoustic model in the Mp3 coding and why Mp3 coding is one of the best, if not the best compression methods out there. A comparison of Mp3 coding with the some what earlier method which is known as Perceptual Coding will also be discussed in the chapters to come. Finally a conclusion section will also be included, stating what I have personally achieved from this experiment as well as from this project itself. Some of the difficulties and challenges that I have encountered while participating in this project will also be included, to highlight to future candidates who might be interested in topics relating to this field of study.